Inflation Expectation Uncertainty, Inflation and the Outputgap - Torsten Schmidt (ZBW - Leibniz-Informationszentrum Wirtschaft, 2018)
This article examines the effect of inflation expectation uncertainty on inflation, inflation expectations and the output gap. For monetary policy, guiding inflation expectations provides an instrument to affect economic conditions. However, expectation uncertainty may undermine monetary policy's ability to stabilise the economy. Using a VAR model with stochastic volatility in mean, this paper shows that inflation expectation uncertainty has negative effects on the inflation rate and the output gap. This result is replicable with a model, in which uncertainty is approximated by a cross-sectional survey measure.
Keywords: E31; C32; 330